Catalysts for exhaust gas purification
By making the particle size of the OSC material larger than that of the non-OSC material in the exhaust purification catalyst and optimizing its composition and structure, the problem of insufficient heat resistance in high-temperature environments is solved, and long-term efficient purification of the catalyst is achieved performance.
Patent Information
- Application Number
- CN202080062866.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-09-02
- Filing Date
- 2020-07-30
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2040-07-30
AI Technical Summary
When the existing catalyst for exhaust purification is exposed to high-temperature exhaust gas for a long time, the heat resistance of the OSC material is insufficient, resulting in a degradation of the catalytic performance with reuse.
By making the particle size of the OSC material larger than that of the non-OSC material in the catalyst layer, the reaction interface is increased, the contact between the catalyst layer and the exhaust gas is improved, and the composition and structure of the OSC material are optimized to improve its heat resistance.
The stable oxygen retention capacity of OSC materials is achieved, the service life of the catalyst is extended, and the exhaust purification performance is improved, especially the purification performance of NOx.
Smart Images

Figure CN114364458B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a catalyst for purifying exhaust gas.
[0002] Furthermore, the present application claims priority based on Japanese Patent Application No. 2019-159780 filed on September 2, 2019, the entire contents of which are incorporated herein by reference. Background Art
[0003] The exhaust gas discharged from an internal combustion engine such as an automobile engine contains harmful components such as hydrocarbons (HC), carbon monoxide (CO), and nitrogen oxides (NOx). In order to efficiently capture and remove these harmful components from the exhaust gas, exhaust gas purification catalysts have been used in the past. As prior art documents related to exhaust gas purification catalysts, for example, Patent Documents 1 to 3 can be cited.
[0004] Patent Document 1 discloses a catalyst for exhaust gas purification, which has a catalyst layer containing two or more carriers of different particle sizes and a precious metal in order to improve gas diffusibility and miscibility in the catalyst layer. Patent Document 1 describes that particles containing silica and alumina are used as a large-particle-size carrier, and an oxygen storage material (OSC material) containing cerium oxide and zirconium oxide and having an oxygen storage capacity (OSC) is used as a small-particle-size carrier.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: International Publication No. 2015 / 037613
[0008] Patent Document 2: Japanese Patent Application Publication No. 9-253454
[0009] Patent Document 3: Japanese Patent Application Publication No. 2017-189735 Summary of the invention
[0010] The OSC material plays a role in alleviating atmosphere fluctuations by occluding oxygen in the exhaust gas when the exhaust gas air-fuel ratio is a lean atmosphere (i.e., an atmosphere with excess oxygen compared to the theoretical air-fuel ratio), and releasing the occluded oxygen when the exhaust gas air-fuel ratio is a rich atmosphere (i.e., an atmosphere with excess fuel compared to the theoretical air-fuel ratio). As a result, stable catalytic performance can be achieved even when the exhaust gas air-fuel ratio changes due to, for example, the driving conditions of the vehicle. As an example of an OSC material, a CeO2-ZrO2 composite oxide can be cited.
[0011] However, in recent years, from the perspective of ensuring the purification of exhaust gas with a small amount of precious metals, the heat resistance of exhaust gas purification catalysts has been required to be improved. However, the existing exhaust gas purification catalysts have the problem that the exhaust gas purification performance decreases with repeated use. The inventors of the present invention have repeatedly conducted in-depth research and found that one of the main reasons can be considered to be the low heat resistance of the OSC material. That is, when the exhaust gas purification catalyst is exposed to high-temperature exhaust gas for a long time, the OSC material is coarsened due to sintering, and the specific surface area is reduced. Due to the reduction in the specific surface area of the OSC material, the number of active sites for absorbing external air and oxygen is reduced, and the speed is reduced. In addition, with sintering, the number of structural defects is reduced (for example, the CeO2-ZrO2 composite oxide as the OSC material undergoes phase separation), and the amount of OSC is reduced. In addition, at this time, if oxygen above the absorption capacity flows into the exhaust gas purification catalyst, due to the reduction in OSC capacity, the theoretical ratio state with the highest ternary activity cannot be maintained. As a result, the exhaust gas becomes an atmosphere with excess oxygen, and the exhaust gas purification performance, especially the purification performance of NOx, is greatly reduced. Moreover, degradation of the carrier and sintering of the noble metal occur, and the surface area of the noble metal decreases, which reduces the catalytic activity. Sintering of the noble metal also occurs as the redox state of the noble metal changes. Therefore, it is important to improve the heat resistance of the carrier, especially the heat resistance of the OSC material.
[0012] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an exhaust gas purifying catalyst having an OSC material with high heat resistance and improved durability.
[0013] According to the present invention, there is provided a catalyst for exhaust gas purification having a substrate and a catalyst layer disposed on the substrate. The catalyst layer comprises a catalyst metal and a supporting material for supporting the catalyst metal. The supporting material comprises an OSC material having an oxygen storage capacity and a carrier other than the OSC material. The volume-based average particle size Dx of the OSC material obtained by electron microscope observation is greater than 1.5 μm and is greater than the volume-based average particle size Dy of the carrier other than the OSC material obtained by electron microscope observation (Dy<Dx).
[0014] By making the particle size of the OSC material different from the particle size of the carrier other than the OSC material, the "surface (interface) of the particle" where the reaction is likely to occur can be increased. The particles mentioned here refer to all particles of the catalyst metal, OSC material, and non-OSC material that constitute the catalyst layer. By increasing the interface within the catalyst layer, the contact between the catalyst layer and the exhaust gas can be improved. In addition, according to the research of the inventors of the present invention, the particle size of the OSC material has a high correlation with the heat resistance. That is, the larger the particle size of the OSC material, the higher the heat resistance. Therefore, by making the particle size of the OSC material larger than the particle size of the carrier other than the OSC material, the heat resistance of the OSC material can be improved. Therefore, in the above-mentioned structure, the OSC material can stably exert its oxygen storage capacity even if it is repeatedly used. As a result, the catalytic performance of the above-mentioned exhaust gas purification catalyst is not easy to decrease, and excellent durability can be achieved.
[0015] In a preferred embodiment of the present invention, the ratio (Dx / Dy) of the average particle size Dx of the OSC material to the average particle size Dy of the carrier other than the OSC material is 1.3 to 20. This can improve gas diffusivity in the catalyst layer and contact between exhaust gas and the OSC material.
[0016] In a preferred embodiment of the present invention, the content of the carrier other than the OSC material is 25 to 200 parts by mass based on 100 parts by mass of the OSC material. This can more appropriately exhibit the above-mentioned effects.
[0017] In a preferred embodiment of the present invention, the average particle size Dy of the carrier other than the OSC material is 3 μm or less. This can more appropriately improve the durability and heat resistance of the catalyst layer.
[0018] In a preferred embodiment of the present invention, the average particle size Dx of the OSC material is 15 μm or less. This ensures wider contact between the exhaust gas and the catalyst layer (eg, OSC material), and can significantly improve exhaust gas purification performance.
[0019] In a preferred embodiment of the present invention, the OSC material is a Ce-containing oxide containing cerium oxide (ceria). When the OSC material contains cerium oxide, the oxygen storage capacity can be improved well.
[0020] In a preferred embodiment of the present invention, the support other than the OSC material is an Al-containing oxide containing alumina. When the support other than the OSC material contains alumina, the heat resistance of the catalyst layer can be improved well.
[0021] In a preferred embodiment of the present invention, the catalyst layer is formed on the surface of the substrate, and a second catalyst layer including a catalyst metal of a different type from that of the catalyst layer is formed on the catalyst layer. This can further improve exhaust gas purification performance.
[0022] In a preferred embodiment of the present invention, the catalyst layer contains Pd as the catalyst metal, and the second catalyst layer contains Rh as the catalyst metal. This can further improve the exhaust gas purification performance.
[0023] In a preferred embodiment of the present invention, the catalyst layer has catalyst layers of different compositions on the upstream side and the downstream side in the flow direction of the exhaust gas from the inlet where the exhaust gas flows in toward the outlet where the exhaust gas flows out. This makes it possible to achieve both high levels of oxygen storage capacity and heat resistance.
[0024] In a preferred embodiment of the present invention, the catalyst layer is divided into two parts in the flow direction of the exhaust gas, the side close to the inlet is the front section, and the side close to the outlet is the rear section, and the carrier other than the OSC material contained in the front section is more than that in the rear section. Thus, the durability (especially heat resistance) of the catalyst layer can be improved, and the oxygen storage capacity and heat resistance can be achieved at a high level for a long time. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram showing an exhaust gas purification system according to a first embodiment.
[0026] Figure 2 It is a perspective view schematically showing the exhaust gas purification catalyst according to the first embodiment.
[0027] Figure 3 It is a partial cross-sectional view schematically showing the structure of the catalyst layer according to the first embodiment.
[0028] Figure 4 It is a cross-sectional view schematically showing a catalyst layer according to the second embodiment.
[0029] Figure 5 This is a graph showing the relationship between the average particle diameter ratio (Dx / Dy) of the supporting material and NOx-T50.
[0030] Figure 6 This is a graph showing the relationship between the average particle size Dy of the non-OSC material and NOx-T50.
[0031] Figure 7 This is a graph showing the relationship between the average particle size Dx of the OSC material and NOx-T50. DETAILED DESCRIPTION
[0032] <First embodiment>
[0033] Hereinafter, preferred embodiments of the present invention will be described with reference to the accompanying drawings. Furthermore, with respect to matters necessary for implementing the present invention other than matters specifically mentioned in this specification, those skilled in the art can grasp them as design matters based on the prior art in the art. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in the art. Furthermore, in the following drawings, the same symbols are used for components / parts that achieve the same functions, and repeated descriptions are sometimes omitted or simplified. The dimensional relationships (length, width, thickness, etc.) in each figure do not necessarily reflect the actual dimensional relationships. Moreover, in this specification, expressions such as "A to B" (A and B are arbitrary numerical values) indicating a range include the meaning of being greater than A and less than B, as well as the meanings of "preferably greater than A" and "preferably less than B".
[0034] Figure 1 Schematic diagram of an exhaust gas purification system 1. The exhaust gas purification system 1 includes an internal combustion engine 2 and an exhaust gas purification device 3. The exhaust gas purification system 1 purifies harmful components such as HC, CO, and NOx contained in the exhaust gas discharged from the internal combustion engine 2 through the exhaust gas purification device 3. In addition, the arrows in the figure indicate the flow direction of the exhaust gas. In the following description, the side close to the internal combustion engine 2 along the flow of the exhaust gas is referred to as the upstream side, and the side away from the internal combustion engine 2 is referred to as the downstream side.
[0035] A mixed gas containing oxygen and fuel gas is supplied to the internal combustion engine 2. The internal combustion engine 2 burns the mixed gas and converts the combustion energy into mechanical energy. The mixed gas after combustion becomes exhaust gas and is discharged to the exhaust purification device 3. In the present embodiment, the internal combustion engine 2 is mainly composed of a gasoline engine of a gasoline vehicle. However, the internal combustion engine 2 may also be an engine other than a gasoline engine. For example, the internal combustion engine 2 may be a diesel engine or an engine mounted on a hybrid vehicle.
[0036] The exhaust purification device 3 has an exhaust passage 4, an engine control unit (Engine Control Unit: ECU) 7, a sensor 8, a first catalyst 9 and a second catalyst 10. Exhaust gas flows in the exhaust passage 4. The exhaust passage 4 of the present embodiment has an exhaust manifold 5 and an exhaust pipe 6. One end (the end on the upstream side) of the exhaust manifold 5 is connected to the exhaust port (not shown) of the internal combustion engine 2. The other end (the end on the downstream side) of the exhaust manifold 5 is connected to the exhaust pipe 6. In the middle of the exhaust pipe 6, the first catalyst 9 and the second catalyst 10 are arranged in sequence from the upstream side. Among them, the arrangement of the first catalyst 9 and the second catalyst 10 can be changed arbitrarily. Moreover, the number of the first catalyst 9 and the second catalyst 10 is not particularly limited, and a plurality of them can be respectively provided. A third catalyst can also be arranged on the downstream side of the second catalyst 10.
[0037] The structure of the first catalyst 9 can be the same as the existing structure and is not particularly limited. The first catalyst 9 can be, for example, an existing well-known oxidation catalyst (DOC), a three-way catalyst, an HC selective reduction type NOx catalyst, a NOx storage reduction catalyst (LNT), a urea selective reduction type NOx catalyst, etc. The first catalyst 9 can have, for example, a function of increasing the temperature of the exhaust gas flowing into the second catalyst 10. In addition, the first catalyst 9 is not a necessary structure and can be omitted. The second catalyst 10 is an example of an exhaust gas purification catalyst disclosed here. The structure of the second catalyst 10 will be described in detail later.
[0038] ECU7 controls the internal combustion engine 2 and the exhaust purification device 3. ECU7 is electrically connected to sensors (e.g., oxygen sensor, temperature sensor, pressure sensor) 8 provided at various locations of the internal combustion engine 2 and the exhaust purification device 3. The information detected by the sensor 8 is received by ECU7 as an electrical signal via an input port (not shown). ECU7 receives information such as the driving state of a gasoline vehicle, the amount of exhaust gas discharged from the internal combustion engine 2, temperature, pressure, etc. ECU7 sends a control signal via an output port (not shown) based on the received information. ECU7 implements operational control such as fuel injection control, ignition control, and intake air volume adjustment control of the internal combustion engine 2. In addition, ECU7 controls the driving and stopping of the exhaust purification device 3 based on the operating state of the internal combustion engine 2, the amount of exhaust gas discharged from the internal combustion engine 2, etc. In addition, the structure of ECU7 can be the same as the existing structure and is not particularly limited. ECU7 is, for example, a processor or an integrated circuit.
[0039] Figure 2 1 is a perspective view of the second catalyst (exhaust purification catalyst) 10. Figure 2 In the figure, the left side is the upstream side (front side) of the exhaust passage 4, and the right side is the downstream side (rear side) of the exhaust passage 4. In addition, the symbol X represents the cylinder axis direction of the exhaust gas purification catalyst 10, in other words, represents the flow direction of the exhaust gas. The exhaust gas purification catalyst 10 is arranged in the exhaust passage 4 in such a way that the cylinder axis direction X is along the flow direction of the exhaust gas. Hereinafter, one direction X1 in the cylinder axis direction X is sometimes referred to as the upstream side (the inlet side, the front side of the exhaust gas), and the other direction X2 is sometimes referred to as the downstream side (the outlet side, the rear side of the exhaust gas).
[0040] The exhaust gas purification catalyst 10 comprises a substrate 11 of a direct current structure and a catalyst layer 20 (see Figure 3 ). In the present embodiment, the substrate 11 has a honeycomb structure. The substrate 11 has a plurality of small chambers (cavities) 12 regularly arranged in the cylinder axis direction X and partition walls (ribs) 14 that separate the plurality of small chambers 12. The end of the exhaust gas purification catalyst 10 in one direction X1 is an exhaust gas inlet 10a, and the end in the other direction X2 is an exhaust gas outlet 10b.
[0041] The substrate 11 constitutes the skeleton of the exhaust gas purification catalyst 10. There is no particular limitation on the substrate 11, and various raw materials and forms of substrates currently used in such applications can be used. For example, the substrate 11 can be appropriately made of a highly heat-resistant material such as cordierite, aluminum titanate, silicon carbide, or an alloy such as stainless steel. In the present embodiment, the outer shape of the substrate 11 is cylindrical. However, the outer shape of the substrate 11 is not particularly limited, and for example, it may be an elliptical cylinder, a polygonal cylinder, a foam, a granular material, a fiber, etc. The volume of the substrate 11 (the apparent volume including the volume of the small chamber 12) can be about 0.1 to 5L, for example, about 0.5 to 2L. Although not particularly limited, the length (total length) of the substrate 11 along the cylinder axis direction X can be about 20 to 500mm, for example, about 50 to 200mm.
[0042] The cell 12 constitutes a flow path for exhaust gas. The cell 12 is along the cylinder axis direction X. The cell 12 is a through hole that penetrates the substrate 11 in the cylinder axis direction X. The shape, size, and number of the cell 12 can be designed, for example, in consideration of the flow rate and composition of the exhaust gas supplied to the exhaust gas purification catalyst 10. There is no particular limitation on the cross-sectional shape orthogonal to the cylinder axis direction X of the cell 12. The cross-sectional shape of the cell 12 can be, for example, a square, parallelogram, rectangle, trapezoid, or other polygonal (for example, triangle, hexagon, octagon), circle, or other geometric shapes. The substrate 11 includes a partition wall 14 that divides the cell 12. The partition wall 14 faces the cell 12 and divides the adjacent cells 12. Although not particularly limited, from the perspective of reducing pressure loss, the thickness of the partition wall 14 (the dimension in the direction orthogonal to the surface. The same applies hereinafter.) can be about 0.1 to 30 mils (1 mil is about 25.4 μm), for example, about 1 to 10 mils.
[0043] Figure 3 This is a partial cross-sectional view that enlarges a portion of the cross section of the exhaust purification catalyst 10 cut along the cylinder axis direction X. In the present embodiment, the catalyst layer 20 is disposed on the surface of the substrate 11 (specifically, on the partition wall 14). The catalyst layer 20 is typically a porous body having a plurality of interconnected voids. The catalyst layer 20 is a portion that purifies the exhaust gas. The exhaust gas flowing into the exhaust purification catalyst 10 contacts the catalyst layer 20 while flowing in the flow path (chamber 12) of the exhaust purification catalyst 10. As a result, harmful components in the exhaust gas are purified. For example, HC and CO contained in the exhaust gas are oxidized by the catalytic function of the catalyst layer 20 and converted (purified) into water, carbon dioxide, etc. In addition, for example, NOx is reduced by the catalytic function of the catalyst layer 20 and converted (purified) into nitrogen.
[0044] The catalyst layer 20 has a catalyst metal (not shown) and a supporting material 21 for supporting the catalyst metal. The catalyst metal is supported on the surface of the supporting material 21. As the catalyst metal, various metal species that play a role as an oxidation catalyst and a reduction catalyst in the purification of harmful components can be used. As a typical example of the catalyst metal, the platinum group, i.e., rhodium (Rh), palladium (Pd), platinum (Pt), ruthenium (Ru), osmium (Os), and iridium (Ir) can be cited. In addition, other metal species such as alkali metals, alkaline earth metals, and transition metals can also be used instead of the platinum group, or in addition to the platinum group. For example, metal species such as iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), silver (Ag), and gold (Au) can be used. In addition, materials alloyed with two or more of these metals can also be used. Among them, an oxidation catalyst with high oxidation activity (such as at least one of Pd and Pt) and a reduction catalyst with high reduction activity (such as Rh) are preferred, and it is particularly preferred to combine them in two or more. The oxidation catalyst and the reduction catalyst can exist in the same (single) catalyst layer.
[0045] From the viewpoint of increasing the contact area with the exhaust gas, the catalyst metal is preferably used in the form of fine particles with a sufficiently small particle size. The average particle size of the catalyst metal (the average value of the particle size obtained by observation with a transmission electron microscope (TEM: Transmission Electron Microscope)) can be about 1 to 15 nm, for example, less than 10 nm, and further less than 5 nm. The amount of catalyst metal carried is calculated in terms of oxide, and can be less than about 20 g, typically 1.5 to 10 g, for example 2.5 g to 5.5 g per 1 L of the volume of the exhaust gas purification catalyst 10 (the volume of the substrate 11). Cost reduction can be achieved by reducing the content of the catalyst metal catalyst. The catalyst metal can be carried uniformly along the axial direction X of the cylinder, or, for example, the carrying amount can be changed in stages from the upstream side to the downstream side.
[0046] The supporting material 21 supports the catalyst metal. The supporting material 21 is typically in powder form (granular form). The supporting material 21 can be an inorganic porous body with a large specific surface area. As the supporting material 21, for example, a metal oxide or a solid solution thereof with excellent heat resistance is preferably used. As typical examples of the supporting material 21, rare earth metal oxides such as aluminum oxide (Al2O3, alumina), titanium oxide (TiO2, titania), zirconium oxide (ZrO2, zirconia), silicon oxide (SiO2, silica), yttrium oxide (Y2O3, yttria), lanthanum oxide (La2O3), cerium oxide (CeO2, ceria), neodymium oxide (Nd2O3), alkaline earth metal oxides such as magnesium oxide (MgO, magnesium oxide), alkali metal oxides, and their solid solutions, such as CeO2-ZrO2 composite oxides containing cerium dioxide and zirconium dioxide, La2O3-Al2O3 composite oxides containing lanthanum oxide and aluminum oxide, etc. can be listed. These may be used alone or in combination of two or more.
[0047] In the present embodiment, the supporting material 21 includes an OSC material 22 having oxygen storage capacity, and a carrier other than the OSC material (hereinafter also referred to as a non-OSC material) 23. The non-OSC material 23 does not have oxygen storage capacity. Catalyst metals are respectively carried on the surfaces of the OSC material 22 and the non-OSC material 23. As a result, for example, the catalyst metal can be dispersed and carried relatively better than when the catalyst metal is carried only on either the OSC material 22 or the non-OSC material 23. Therefore, the degradation of the catalyst metal (for example, sintering accompanying particle growth) can be suppressed, and the durability of the exhaust gas purification catalyst 10 can be improved.
[0048] Typically, the composition of the OSC material 22 and the non-OSC material 23 is different. Usually, the non-OSC material 23 is relatively less susceptible to structural changes associated with oxidation-reduction, and therefore, typically has higher heat resistance than the OSC material 22. In addition, the heat resistance of the support material 21 can be confirmed, for example, by the degree of reduction in specific surface area after exposure to a specific temperature (e.g., 1000°C). From the viewpoint of suppressing the degradation associated with the use of the exhaust purification catalyst 10 over the years, the components (e.g., oxides) that constitute the main body (the component that accounts for the largest proportion by mass ratio, preferably a component that accounts for 50% by mass or more) of the OSC material 22 and the non-OSC material 23 can be made different.
[0049] The OSC material 22 may be a metal oxide (containing Ce oxide) containing cerium oxide having high oxygen storage capacity. The OSC material 22 may be composed, for example, of at least one of zirconium, titanium and silicon as the main body. The Ce-containing oxide may be cerium oxide, and / or a composite oxide of cerium oxide and a metal oxide other than cerium oxide. From the viewpoint of improving the heat resistance of the OSC material 22, a CeO2-ZrO2 composite oxide is preferred. The CeO2-ZrO2 composite oxide may be mainly composed of Ce or Zr. When the CeO2-ZrO2 composite oxide is set to 100% by mass as a whole, the mixing ratio of cerium oxide may be approximately 1 to 60% by mass, typically 5 to 55% by mass, preferably 10 to 50% by mass, for example 15 to 45% by mass. When the mixing ratio of cerium oxide is above a specified value, the oxygen storage capacity is improved. When the mixing ratio of cerium oxide is below a specified value, the heat resistance is improved. When it is within the above range, it is possible to take into account both oxygen storage capacity and heat resistance at a high level. In addition, from the viewpoint of improving heat resistance, the CeO2-ZrO2 composite oxide may further contain metal oxides other than CeO2, such as rare earth metal oxides. In addition, when the OSC material 22 is a Ce-containing oxide, the non-OSC material 23 may be a metal oxide (non-Ce oxide) that does not contain cerium oxide.
[0050] In some embodiments, the non-OSC material 23 may be an inorganic oxide with high durability (especially heat resistance). For example, it may be a metal oxide containing Al (containing Al oxide) or a metal oxide containing Zr (containing Zr oxide). From the perspective of improving the heat resistance of the non-OSC material 23, the non-OSC material 23 may be mainly composed of an inorganic oxide (such as aluminum oxide, zirconium oxide). By using an inorganic oxide with high heat resistance as the main body, for example, high heat resistance can be maintained even if the average particle size is small. Alumina may be γ-alumina, δ-alumina, θ-alumina, α-alumina, etc. Al-containing oxides may include, for example, aluminum oxide, and / or a composite oxide of aluminum oxide and a metal oxide other than aluminum oxide (such as a rare earth metal oxide). When such a composite oxide is set to 100% by mass as a whole, the mixing ratio of metal oxides other than aluminum oxide may be approximately less than 50% by mass, typically 0.1 to 20% by mass, for example 1 to 10% by mass. In addition, when the non-OSC material 23 is an oxide containing Al, the OSC material 22 may be a metal oxide (non-Al oxide) not containing aluminum oxide.
[0051] In the present embodiment, the average particle diameters of the OSC material 22 and the non-OSC material 23 are different. Specifically, the average particle diameter Dx of the OSC material 22 is larger than the average particle diameter Dy of the non-OSC material 23. That is, Dx and Dy satisfy Dy<Dx. Furthermore, in the present specification, the "average particle diameter Dx, Dy" of the supporting material 21 in the catalyst layer 20 refers to: the cross-section of the catalyst layer 20 is observed by an electron microscope, and the observed image is analyzed by the image processing software Image J, and the volume frequency distribution based on the volume basis is obtained, which is equivalent to the particle diameter when the accumulation is 50% from the small particle diameter side. The detailed calculation method is described in the examples.
[0052] The ratio (Dx / Dy) of the average particle size Dx of the OSC material 22 to the average particle size Dy of the non-OSC material 23 may be greater than 1, approximately 1.1 or more, 1.2 or more, preferably 1.3 or more, for example, 1.5 or more, approximately 50 or less, for example, 20 or less, 15 or less, 10 or less, 7 or less, or 5 or less. By making the above ratio greater than a specified value, the catalyst layer 20 can be appropriately densified and the thickness of the catalyst layer 20 can be reduced. Thus, the pressure loss can be reduced. By making the above ratio less than a specified value, the catalyst layer 20 can be prevented from becoming too dense, and the gas diffusivity in the catalyst layer 20 and the contact between the exhaust gas and the OSC material 22 can be improved.
[0053] The average particle size Dx of the OSC material 22 is greater than 1.5 μm. Typically, there is a tendency that the larger the average particle size Dx, the higher the heat resistance. Therefore, by making the average particle size Dx greater than a specified value, the OSC material 22 can be given a heat resistance greater than a specified value. The average particle size Dx of the OSC material 22 is preferably greater than 1.6 μm, for example, greater than 1.65 μm, greater than 1.7 μm, greater than 1.8 μm, greater than 1.9 μm, greater than 1.95 μm, and can be about 20 μm or less, preferably less than 15 μm, less than 14 μm, for example, less than 10 μm, less than 5 μm, or less than 4 μm. By making the value of Dx within the above range, it is possible to ensure that the exhaust gas has a wide contact with the catalyst layer 20 (for example, the OSC material 22), and the purification performance can be improved. Therefore, the effect of the technology disclosed herein can be exerted at a higher level.
[0054] Although not particularly limited, the average particle size Dy of the non-OSC material 23 can be about 0.1 μm or more, preferably 0.3 μm or more, for example, 0.5 μm or more, 0.7 μm or more, about 5 μm or less, preferably 3 μm or less, for example, 2 μm or less, 1.5 μm or less. By making the value of Dy within the above range, the durability and heat resistance of the catalyst layer 20 (especially the non-OSC material 23) can be well improved. It is also possible to prevent the catalyst layer 20 from becoming too dense and improve the gas diffusion in the catalyst layer 20. Therefore, the effect of the technology disclosed here can be exerted at a higher level.
[0055] In the catalyst layer 20, for example, the OSC material 22 may be the main body, or the non-OSC material 23 may be the main body. Although not particularly limited, in the catalyst layer 20, when the OSC material 22 is set to 100 parts by mass, the content ratio of the non-OSC material 23 may be about 5 parts by mass or more, preferably 10 parts by mass or more, 20 parts by mass or more, for example, 25 parts by mass or more, and about 500 parts by mass or less, preferably 300 parts by mass or less, for example, 200 parts by mass or less. The content ratio of the OSC material 22 to the non-OSC material 23 may be, for example, 1:10 to 10:1, 1:5 to 5:1, 1:2 to 2:1. By setting it to the above range, it is possible to prevent the catalyst layer 20 from becoming too dense, and improve the gas diffusivity in the catalyst layer 20 and the contact between the exhaust gas and the OSC material 22.
[0056] Although not particularly limited, the molding amount (coating amount) of the support material 21 in the catalyst layer 20 can be about 30 to 300 g, preferably 50 to 200 g, for example, 100 to 150 g per 1 L of the volume of the exhaust gas purifying catalyst 10 (the volume of the substrate 11). The coating amount of the OSC material 22 in the catalyst layer 20 can be about 5 to 200 g, preferably 30 to 150 g, for example, 40 to 80 g per 1 L of the volume of the exhaust gas purifying catalyst 10 (the volume of the substrate 11). The coating amount of the non-OSC material 23 in the catalyst layer 20 can be about 10 to 200 g, preferably 30 to 150 g, for example, 40 to 80 g per 1 L of the volume of the exhaust gas purifying catalyst 10 (the volume of the substrate 11). By making the coating amount greater than the specified value, it is possible to suppress the catalyst layer 20 from becoming too dense and improve the gas diffusion in the catalyst layer 20. By making the coating amount less than the specified value, the pressure loss of the catalyst layer 20 can be reduced. By satisfying the above range, it is possible to achieve both reduction in pressure loss and improvement in exhaust gas purification performance at a high level. In addition, in this specification, "molding amount" refers to the mass of solid content contained per unit volume.
[0057] The catalyst layer 20 may contain any component in addition to the catalyst metal and the support material 21. In the case where the catalyst layer 20 contains an oxidation catalyst (for example, at least one of Pd and Pt) as the catalyst metal, it is preferable to contain alkaline earth elements such as calcium (Ca) and barium (Ba). As a result, the oxygen absorption amount under a lean atmosphere can be further increased. In addition, the oxidation catalyst poisoning can be appropriately suppressed, and the catalyst activity can be improved. The dispersibility of the oxidation catalyst can also be improved, and the particle growth of the oxidation catalyst can be suppressed at a high level. Alkaline earth elements typically exist in the catalyst layer 20 in the form of oxides. When the content of the alkaline earth element is converted into barium sulfate, it can be about 0.1 to 30 g, preferably 0.5 to 20 g, for example 1 to 15 g per 1L of the volume of the exhaust gas purification catalyst 10 (the volume of the substrate 11). In addition, when the OSC material 22 is set to 100 parts by mass, the content of the alkaline earth element can be about 10 to 200 parts by mass, preferably 20 to 150 parts by mass, for example 30 to 150 parts by mass.
[0058] In addition, as an example of an arbitrary component that can be contained in the catalyst layer 20, for example, an OSC material that does not carry a catalyst metal, a non-OSC material that does not carry a catalyst metal, a NOx adsorption material having a NOx absorption capacity, a stabilizer, etc. can be listed. In some embodiments, the catalyst layer 20 contains a stabilizer. As a stabilizer, for example, rare earth elements other than Ce such as yttrium (Y), lanthanum (La), and neodymium (Nd) can be listed. As a result, the specific surface area of the catalyst layer 20 at high temperature can be increased without hindering the catalytic function. Rare earth elements are typically present in the catalyst layer 20 in the form of oxides.
[0059] The thickness of the catalyst layer 20 can be appropriately designed according to the size of the cells 12 of the substrate 11, for example. In some embodiments, the thickness of the catalyst layer 20 is about 5 to 500 μm, preferably 10 to 200 μm, for example 30 to 100 μm. This can achieve both a high level of pressure loss reduction and an improvement in exhaust gas purification performance.
[0060] The catalyst layer 20 does not necessarily need to be uniform over the total length of the substrate 11 in the axial direction X. In the axial direction X, the catalyst layer 20 may be provided continuously or intermittently in a portion corresponding to about 20% or more, preferably 40 to 100%, for example 50 to 80% of the total length of the substrate 11. Thus, the effect of the technology disclosed herein can be exerted at a higher level.
[0061] The exhaust gas purification catalyst 10 may have more than two catalyst layers. In this case, it is sufficient as long as at least one of the layers satisfies the composition of the catalyst layer 20. The catalyst layer 20 may be one layer or more than two layers. In addition, there may be catalyst layers other than the catalyst layer 20, layers that are not catalyst layers, such as layers that do not contain catalyst metals, etc. The exhaust gas purification catalyst 10 may have other catalyst layers different from the catalyst layer 20 in the cylinder axis direction X, for example. In some embodiments, the exhaust gas purification catalyst 10 may be provided with catalyst layers of different compositions in various parts of the substrate 11, for example, on the upstream side X1 and the downstream side X2 in the cylinder axis direction X. In this case, the catalyst layer 20 may be located in any part. The catalyst layer 20 may be provided, for example, from the exhaust gas inlet 10a along the cylinder axis direction X, or from the exhaust gas outlet 10b along the cylinder axis direction X.
[0062] In addition, the manufacturing method of the exhaust gas purification catalyst 10 can be the same as the prior art except that the average particle size of the supporting material 21 used for the catalyst layer forming slurry is pre-adjusted. The exhaust gas purification catalyst 10 can be manufactured, for example, by the following method. That is, first, prepare a substrate 11 and a slurry for forming a catalyst layer 20. The slurry can be prepared separately for each forming layer as needed. The catalyst layer forming slurry can be prepared by dispersing the catalyst metal source (for example, a solution containing a catalyst metal in the form of ions) and the above-mentioned two kinds of supporting materials 21 (i.e., OSC material 22 and non-OSC material 23) as necessary raw material components, and other arbitrary components, such as adhesives, various additives, etc. in a dispersion medium. As an adhesive, for example, alumina sol, silica sol, etc. can be used. As a dispersion medium, for example, water and an aqueous solvent can be used. The properties of the slurry, such as viscosity, solid content, etc., can be appropriately adjusted according to the size of the substrate 11 used, the shape of the small chamber 12 (partition wall 14), and the characteristics required for the catalyst layer 20.
[0063] The average particle size of the supporting material 21 (as a raw material) used in the catalyst layer forming slurry is preferably adjusted in advance by, for example, conventionally known wet pulverization or dry pulverization. The average particle size of the supporting material 21 (as a raw material) used in the catalyst layer forming slurry as a whole can be adjusted to about 0.01 to 50 μm, preferably 0.05 to 30 μm, for example 0.1 to 20 μm. The average particle size Db of the non-OSC material 23 (as a raw material) can be adjusted to about 0.01 μm or more, preferably 0.05 μm or more, for example 0.1 μm or more, to about 10 μm or less, preferably 5 μm or less, further 3 μm or less, 2 μm or less, for example 1 μm or less. The average particle size Da of the OSC material 22 (as raw material) can typically be adjusted to be larger than the average particle size Db of the non-OSC material 23, approximately 1 μm or more, preferably 2 μm or more, for example 4 μm or more, and approximately 30 μm or less, preferably 20 μm or less, for example 15 μm or less.
[0064] The ratio (Da / Db) of the average particle diameter Da of the OSC material 22 to the average particle diameter Db of the non-OSC material 23 may be greater than 1, preferably 1.2 or more, 1.3 or more, 1.5 or more, for example 2 or more, and further 5 or more, and may be approximately 100 or less, 90 or less, preferably 50 or less, 40 or less, for example 20 or less, 15 or less. Thus, the composition of the catalyst layer 20 after firing, for example, the following relationship: (average particle diameter Dy of the non-OSC material 23) < (average particle diameter Dx of the OSC material 22) can be appropriately achieved. In addition, a large number of micrometer-level voids (for example, voids with a diameter of about 5 to 10 μm) can be formed in the catalyst layer 20, and the diffusibility of the exhaust gas can be improved. The "average particle diameter Da, Db" of the support material 21 (as a raw material) in the catalyst layer forming slurry refers to the particle diameter (equivalent spherical volume diameter) corresponding to 50% accumulation from the small particle diameter side in the volume-based particle size distribution measured by the laser diffraction / scattering method. Therefore, the average particle diameters Da and Db are typically different from the average particle diameters Dx and Dy of the catalyst layer 20 after firing.
[0065] Next, the prepared catalyst layer forming slurry is flowed into the chamber 12 from the end of the substrate 11 and supplied to a specified length along the cylindrical axis direction X. The slurry can flow in from any side of the inlet 10a and the outlet 10b. For example, the slurry can flow in from the inlet 10a and be supplied to a specified length toward the downstream side X2. In addition, the slurry can also flow in from the outlet 10b and be supplied to a specified length toward the upstream side X1. At this time, the remaining slurry can be sucked from the end on the opposite side. It is also possible to supply air from the end on the opposite side to discharge the remaining slurry from the chamber 12. Then, each time a slurry is supplied, the substrate 11 supplied with the slurry can be dried and fired at a specified temperature and time. The drying and firing methods can be the same as those of the prior art. As a result, the raw material components are sintered to form a porous catalyst layer 20 on the substrate 11. By operating as described above, a catalyst layer 20 can be formed on the surface of the partition wall 14 of the substrate 11.
[0066] <Second embodiment>
[0067] Figure 4 This is an enlarged cross-sectional view of a section obtained by cutting the exhaust gas purification catalyst 30 of the second embodiment along the cylinder axis direction X. The exhaust gas purification catalyst 30 of this embodiment includes a substrate 31 and a catalyst layer 40 of a multilayer structure provided on the surface of the substrate 31. The substrate 31 may be the same as the substrate 11 of the first embodiment described above. And, Figure 4 The illustration of the catalyst metal and the supporting material 21 is omitted. Hereinafter, the catalyst layer 40 is sometimes divided into two parts in the cylinder axis direction X, and the side close to the inlet 10a is called the front section, and the side close to the outlet 10b is called the rear section. In addition, the description of the parts common to the first embodiment is omitted or simplified, and the parts different from the first embodiment are mainly described.
[0068] The catalyst layer 40 is formed into a laminated structure having at least two layers, namely, a lower layer 41 in contact with the surface of the substrate 31 and an upper layer 42 disposed on the surface of the lower layer 41. In the present embodiment, the upper layer 42 constitutes the surface layer portion of the laminated structure of the catalyst layer 40. In the laminated direction of the catalyst layer 40, for example, one or more other layers may be further disposed on the surface of the upper layer 42, between the lower layer 41 and the upper layer 42, between the substrate 31 and the lower layer 41, etc.
[0069] In some embodiments, at least the lower layer 41 satisfies the configuration of the catalyst layer 20 of the first embodiment. For example, only the lower layer 41 may satisfy the configuration of the catalyst layer 20 of the first embodiment, or the lower layer 41 and the upper layer 42 may each satisfy the configuration of the catalyst layer 20 of the first embodiment. However, only the upper layer 42 may satisfy the configuration of the catalyst layer 20 of the first embodiment. Typically, the lower layer 41 and the upper layer 42 are each a catalyst layer having a catalyst metal and a supporting material 21 supporting the catalyst metal.
[0070] The lower layer 41 may contain an oxidation catalyst (for example, at least one of Pd and Pt) as a catalyst metal. The upper layer 42 may contain a catalyst metal of a different type from that of the lower layer 41, for example, a reduction catalyst. Among them, Pd may be loaded on the lower layer 41, and Rh may be loaded on the upper layer 42. By loading the oxidation catalyst and the reduction catalyst separately in the stacking direction, it is possible to suppress the degradation of the catalyst metal (for example, sintering accompanying particle growth), thereby improving the durability of the exhaust gas purification catalyst 10. The amount of catalyst metal loaded in the upper layer 42 may be less than the amount of catalyst metal loaded in the lower layer 41. In addition, the oxidation catalyst and the reduction catalyst may exist in the same layer. For example, the lower layer 41 and the upper layer 42 may each contain an oxidation catalyst and a reduction catalyst.
[0071] In the present embodiment, the lower layer 41 includes an inlet lower layer 41a located on the upstream side X1 of the cylinder axis direction X and an outlet lower layer 41b located on the downstream side X2. The inlet lower layer 41a and the outlet lower layer 41b each satisfy the composition of the catalyst layer 20 of the first embodiment described above. Among them, the lower layer 41 may be composed of a single layer, or may further include 1 or more other layers. In addition, one of the inlet lower layer 41a and the outlet lower layer 41b may satisfy the composition of the catalyst layer 20 of the first embodiment described above. Typically, the inlet lower layer 41a and the outlet lower layer 41b are each catalyst layers having a catalyst metal and a supporting material 21 supporting the catalyst metal. The supporting materials 21 of the inlet lower layer 41a and the outlet lower layer 41b may each contain an OSC material 22 and a non-OSC material 23.
[0072] The compositions of the entry-side lower layer 41a and the exit-side lower layer 41b are different from each other. For example, at least one of the type of catalyst metal, the amount of catalyst metal carried, the type of carrying material 21, the amount of coating of the carrying material 21, the amount of coating of the OSC material 22, and the amount of coating of the non-OSC material 23 is different. In some embodiments, the amount of catalyst metal carried by the entry-side lower layer 41a is greater than the amount of catalyst metal carried by the exit-side lower layer 41b. In this case, the amount of catalyst metal carried is the rear section < the front section. The amount of catalyst metal carried by the entry-side lower layer 41a may be, for example, more than 1.5 times, more than 2 times, for example, 2 to 5 times the amount of catalyst metal carried by the exit-side lower layer 41b. In addition, in some embodiments, the catalyst metal is uniformly carried along the cylinder axis direction X, and the amount of catalyst metal carried by the entry-side lower layer 41a is the same as the amount of catalyst metal carried by the exit-side lower layer 41b.
[0073] In addition, in some embodiments, the coating amount of the supporting material 21 of the lower layer 41a on the inlet side is less than the coating amount of the supporting material 21 of the lower layer 41b on the outlet side. In this case, the coating amount of the supporting material 21 is the rear section < the front section. Thus, the pressure loss when the exhaust gas flows into the small chamber 12 can be reduced. In addition, in some embodiments, the coating amount of the OSC material 22 of the lower layer 41a on the inlet side is less than the coating amount of the OSC material 22 of the lower layer 41b on the outlet side. In this case, the coating amount of the OSC material 22 is the front section < the rear section. On the contrary, the coating amount of the non-OSC material 23 of the lower layer 41a on the inlet side is more than the coating amount of the non-OSC material 23 of the lower layer 41b on the outlet side. In this case, the coating amount of the non-OSC material 23 is the rear section < the front section. Thus, the durability (especially heat resistance) of the supporting material 21 can be improved, and the oxygen storage capacity and heat resistance can be achieved at a high level for a long time.
[0074] Although not particularly limited, the inlet-side lower layer 41a may be provided continuously along the cylinder axis direction X from the inlet 10a to a portion corresponding to about 25% or more, preferably 40 to 100%, for example, 50 to 80% of the total length L of the substrate 31. In addition, the outlet-side lower layer 41b may be provided continuously along the cylinder axis direction X from the outlet 10b to a portion corresponding to about 25% or more, preferably 40 to 100%, for example, 50 to 80% of the total length L of the substrate 31. Figure 4In the figure, the inlet lower layer 41a is formed at a portion corresponding to 50% of the total length L of the substrate 31 from the inlet 10a of the substrate 31 toward the outlet 10b (La=1 / 2L). In addition, the outlet lower layer 41b is formed at a portion corresponding to 50% of the total length L of the substrate 31 from the outlet 10b of the substrate 31 toward the inlet 10a (Lb=1 / 2L). The lower layer 41 is continuously formed on the surface of the substrate 31 with a length equal to the total length L. In addition, the inlet lower layer 41a and the outlet lower layer 41b may overlap partially near the center in the cylindrical axial direction X. For example, near the center in the cylindrical axial direction X, the inlet lower layer 41a and the outlet lower layer 41b may be stacked in the vertical direction with a length of approximately 1 / 10L to 1 / 3L, for example, 1 / 5L to 1 / 4L, or a three-layer structure may be formed by the inlet lower layer 41a, the outlet lower layer 41b and the upper layer 42.
[0075] The supporting material 21 of the upper layer 42 may contain an OSC material 22 and a non-OSC material 23, for example, it may not contain either one. In some embodiments, by containing an OSC material in both the lower layer 41 and the upper layer 42, the contact between the exhaust gas and the OSC material 22 can be improved, and the effect of alleviating the atmosphere change can be effectively improved. In addition, in some embodiments, the coating amount of the OSC material 22 of the upper layer 42 is greater than the coating amount of the OSC material 22 of the lower layer 41a on the inlet side. In some embodiments, the coating amount of the OSC material 22 of the upper layer 42 is less than the coating amount of the OSC material 22 of the lower layer 41b on the outlet side. In some embodiments, the coating amount of the non-OSC material 23 of the upper layer 42 is less than the coating amount of the non-OSC material 23 of the lower layer 41a on the inlet side. In some embodiments, the coating amount of the non-OSC material 23 of the upper layer 42 is greater than the coating amount of the non-OSC material 23 of the lower layer 41a on the outlet side. Thereby, it is possible to achieve both oxygen storage capacity and heat resistance at a high level for a long period of time.
[0076] As described above, the exhaust gas purification catalyst 10, 30 can ensure appropriate gaps in the catalyst layer 20, 40 and improve the heat resistance of the OSC material 22. Therefore, in the above-mentioned structure, the contact between the exhaust gas and the OSC material 22 is good, and even if it is repeatedly used, the OSC material 22 can stably exert the oxygen storage capacity. As a result, the catalytic performance of the exhaust gas purification catalyst 10, 30 is not easily reduced, and excellent purification performance can be achieved for a long time.
[0077] Hereinafter, test examples related to the present invention will be described; however, the present invention is not limited to the embodiments shown in the following test examples.
[0078] [Test Example 1: Study on a single layer]
[0079] (Example 1)
[0080] In this embodiment, a catalyst layer of a single-layer structure is formed on a substrate using a slurry. Specifically, first, a honeycomb substrate (cordierite, volume: 700 mL, total length of substrate: 84 mm, number of cells: 600 cells, cell shape: hexagonal, thickness of partition wall: 2 mils) is prepared. In addition, in the following description, "L-cat" refers to the solid content per 1L of the volume of the exhaust gas purification catalyst (volume of the substrate).
[0081] Next, the following two types of powders were prepared as supporting materials.
[0082] OSC material: CeO2-ZrO2 composite oxide, CeO2 = 15-45% by mass, with trace amounts of Nd2O3, La2O3, Y2O3, Pr6O 11 , high heat resistance has been implemented.
[0083] Non-OSC material: La2O3-Al2O3 composite oxide, La2O3=1 to 10% by mass.
[0084] Next, the two kinds of powders were wet-pulverized to adjust the average particle size Da of the OSC material to 9 μm and the average particle size Db of the non-OSC material to 0.5 μm. The average particle sizes Da and Db after pulverization were measured using a laser diffraction / scattering particle size distribution analyzer LA-960 (manufactured by HORIBA).
[0085] Next, a Pd nitrate solution (2.0 g / L-cat in terms of Pd) and a Rh nitrate solution (0.2 g / L-cat in terms of Rh), a non-OSC material (Db = 0.5 μm, 120 g / L-cat), an OSC material (Da = 9 μm, 120 g / L-cat), barium sulfate (10 g / L-cat) and an Al2O3-based binder are dispersed in an aqueous solvent and stirred and mixed to prepare slurry 1. Next, slurry 1 is flowed into the upstream end of the honeycomb substrate, and the unnecessary part is blown away with a blower, and the material is applied to a portion corresponding to 100% of the total length of the partition wall. It is heated and dried in a dryer at 120°C for 2 hours, and after removing the moisture, it is fired in an electric furnace at 500°C for 2 hours. In this way, a catalyst for exhaust gas purification of Example 1 having a catalyst layer formed on the surface of the substrate is obtained. Furthermore, in the catalyst layer of Example 1, when the OSC material is 100 parts by mass, the content ratio of the non-OSC material is 100 parts by mass (non-OSC material:OSC material=1:1).
[0086] (Comparative Example 1)
[0087] In Comparative Example 1, all conditions were the same as those in Example 1 except for the particle size of the raw material. That is, La2O3-Al2O3 composite oxide with Db=7μm was used as the non-OSC material, and CeO2-ZrO2 composite oxide with Da=3μm was used as the OSC material, slurry 2 was prepared, and the catalyst layer was formed. The exhaust gas purification catalyst of Comparative Example 1 was obtained in the same manner as in Example 1. The exhaust gas purification catalysts involved in each example are summarized in Table 1.
[0088] [Measurement of average particle diameter Dx and Dy of supported material]
[0089] The above-mentioned catalyst for exhaust purification is cut along the axial direction of the cylinder to cut out a test piece. After embedding and grinding the test piece, a scanning electron microscope (SEM: Scanning Electron Microscope) is used to observe the cross-section of the substrate and the catalyst layer to obtain an observation image. Among them, the observation magnification is based on 1000 times. When the particle size is small, the observation magnification is further increased to 4000 times and 8000 times for observation. Then, the observation image is read using the open source image analysis software Image J, and the image analysis is performed through the following steps to measure the average particle sizes Dx and Dy of non-OSC materials and OSC materials respectively. The results are shown in Table 1.
[0090] (1) Open the SEM reflection electron image file.
[0091] (2) Draw lines according to the scale.
[0092] (3) Use Set Scale to match pixels and length (μm).
[0093] (4) Cut out the image of the catalyst layer portion to be analyzed.
[0094] (6) The brightness is automatically binarized by adjusting the threshold. In this way, the non-OSC material and the OSC material are automatically segmented and classified into white for the non-OSC material and black for the OSC material.
[0095] (7) For the OSC material (black) portion, fine adjustments were made by manually removing the gaps, etc. Then, the following (8) to (14) were performed for each of the non-OSC material and the OSC material.
[0096] (8) Use watershed to automatically split connected particles.
[0097] (9) Use analyze particle to obtain the area of each segmented particle. The analysis range is 0 to infinity (μm 2), the roundness is 0 to 1.0, the particles at the image end are excluded, and the calculation includes the hollow particles with open pores.
[0098] (10) Use Distribution to represent the frequency distribution of the area. The range is 0.005 to 30000 (μm 2 ), the number of divisions is 7.2 million.
[0099] (11) The obtained frequency distribution of the area is converted into the particle size (diameter) by perfect circle approximation.
[0100] (12) Calculate the volume using a spherical approximation based on the particle size and multiply the volume by the frequency.
[0101] (13) The total volume of the particles is accumulated and the volume fraction of each particle size is calculated as the volume frequency.
[0102] (14) The particle size and volume frequency are plotted to create a volume frequency distribution, and the point where the cumulative volume frequency reaches 50% from the small particle size side is taken as the average particle size (volume basis).
[0103] [Evaluation of NOx purification performance]
[0104] The exhaust gas purification catalyst involved in each example was installed in a V-type 8-cylinder (displacement: 4600cc) gasoline engine, and a 50-hour durability test was carried out at an average engine speed of 3000rpm and a catalyst bed temperature of 1000℃. After the durability test, the NOx purification performance of the simulated exhaust gas of a gasoline vehicle was evaluated using a catalyst evaluation device with an L-type 4-cylinder (displacement: 2500cc). The catalyst evaluation device can analyze the components of the gas flowing into the exhaust gas purification catalyst and the gas flowing out of the exhaust gas purification catalyst. Specifically, the exhaust gas purification catalyst involved in each example was set in the catalyst evaluation device, and the temperature rise characteristics from room temperature (25℃) to 600℃ (temperature rise rate 20℃ / min) were measured while supplying simulated exhaust gas with an air-fuel ratio (A / F) of 14.6 at an average engine speed of 3000rpm. The NOx purification rate was measured based on the NOx concentration ratio in the inflow gas and the outflow gas at this time. In addition, the temperature (NOx-T50) at which the NOx purification rate reaches 50% was calculated. The results are shown in Table 1.
[0105] [Table 1]
[0106] Table 1 Research on single layer
[0107]
[0108] As shown in Table 1, the exhaust gas purification catalyst of Example 1 with 1.5 μm ≤ Dx and Dy < Dx has significantly lower NOx-T50 than the exhaust gas purification catalyst of Comparative Example 1 with Dy > Dx. That is, the NOx purification performance after durability is high. As a reason for this, it can be considered that by making the particle size of the OSC material larger than that of the non-OSC material, the heat resistance of the OSC material is improved, and the degradation of the OSC material after durability is suppressed.
[0109] [Test Example 2: Study on the lower layer of the upper and lower two-layer structure]
[0110] (Example 2)
[0111] In the present embodiment, two types of slurries having different compositions are used to form a catalyst layer having a two-layer structure of upper and lower layers on a substrate.
[0112] Specifically, first, the same OSC material, non-OSC material and honeycomb substrate as in Example 1 were prepared. Next, a Pd nitrate solution (0.6 g / L-cat in terms of Pd), a non-OSC material (Db = 0.5 μm, 35 g / L-cat), an OSC material (Da = 9 μm, 50 g / L-cat), barium sulfate (5 g / L-cat) and an Al2O3-based binder were dispersed in an aqueous solvent and stirred and mixed to prepare slurry 3. Next, the slurry 3 was flowed into the upstream end of the honeycomb substrate, and the unnecessary part was blown off with a blower, and the material was applied to a part corresponding to 90% of the total length of the partition wall. It was heated and dried in a 120°C dryer for 2 hours, and after removing the moisture, it was fired in an electric furnace at 500°C for 2 hours to form a lower layer from the upstream side along the cylinder axis direction X.
[0113] Next, Rh nitric acid solution (0.4 g / L-cat in terms of Rh), non-OSC material (Dy = 7 μm, 60 g / L-cat), OSC material (Dx = 3 μm, 70 g / L-cat) and Al2O3-based binder are dispersed in an aqueous solvent and stirred to prepare slurry 4. Next, slurry 4 is flowed into the end of the upstream side of the substrate having the above-mentioned catalyst layer, and the unnecessary part is blown away with a blower, and the material is applied to a portion equivalent to 100% of the total length of the partition wall. It is heated and dried in a dryer at 120°C for 2 hours, and after removing the moisture, it is fired in an electric furnace at 500°C for 2 hours to form an upper layer from the upstream side along the cylinder axis direction X. In this way, an exhaust gas purification catalyst of Example 2 having two catalyst layers, a lower layer formed on the surface of the substrate (90% of the total length of the partition wall) and an upper layer formed on the surface of the lower layer (100% of the total length of the partition wall) is obtained.
[0114] (Comparative Example 2)
[0115] In Comparative Example 2, all conditions were the same as those in Example 2 except for the particle size of the raw material of the lower layer. That is, when forming the lower layer, La2O3-Al2O3 composite oxide with Db=7μm was used as a non-OSC material, and CeO2-ZrO2 composite oxide with Da=3μm was used as an OSC material to prepare a slurry. The same operation as in Example 2 was performed to obtain the exhaust gas purification catalyst of Comparative Example 2. In addition, the same operation as in Test Example 1 was performed to measure the average particle size Dx and Dy of the supporting material and evaluate the NOx purification performance. The results are shown in Table 2.
[0116] [Table 2]
[0117] Table 2 Research on the lower layer
[0118]
[0119] In the exhaust purification catalyst of Example 2, the lower layer satisfies 1.5μm≤Dx and Dy<Dx. In the exhaust purification catalyst of Comparative Example 2, both the upper layer and the lower layer do not satisfy 1.5μm≤Dx and Dy<Dx. As shown in Table 2, compared with the exhaust purification catalyst of Comparative Example 2, the NOx-T50 value of the exhaust purification catalyst of Example 2 is a relatively low temperature. That is, the NOx purification performance after durability is high. Therefore, it can be seen that in the case where the exhaust purification catalyst has a catalyst layer with a stacked structure of more than two layers, at least one layer satisfies Dy<Dx, so that the effect of the technology disclosed here can be exerted.
[0120] [Test Example 3: Study on the lower layer of the upper and lower two-layer structure]
[0121] (Example 3)
[0122] In this embodiment, three slurries with different compositions are used to form catalyst layers (lower layers) with different compositions on the upstream and downstream sides of the exhaust gas flow direction on the substrate, and then an upper layer is formed thereon to form a catalyst layer with an upper and lower two-layer structure.
[0123] Specifically, first, prepare the same substrate as in Example 1. Then, as a nitric acid Pd solution (0.5 g / L-cat in terms of Pd), the content of non-OSC material is 30 g / L-cat, the content of OSC material is 50 g / L-cat), and the content of barium sulfate is 15 g / L-cat. The same operation as slurry 1 is performed to prepare slurry 5. Next, slurry 5 is flowed into the end of the outlet side of the above-mentioned honeycomb substrate, and the unnecessary part is blown away with a blower, and the material is applied to a part equivalent to 70% of the total length of the partition wall. It is heated and dried in a dryer at 120°C for 2 hours, and after removing the moisture, it is fired in an electric furnace at 500°C for 2 hours to form an outlet lower layer from the downstream side along the cylinder axis direction X.
[0124] Next, a Pd nitrate solution (1.5 g / L-cat in terms of Pd), a non-OSC material (Db = 0.5 μm, 55 g / L-cat), an OSC material (Da = 9 μm, 15 g / L-cat), barium sulfate (15 g / L-cat) and an Al2O3-based binder are dispersed in an aqueous solvent and stirred to prepare a slurry 6. Next, the slurry 6 is flowed into the upstream end of the substrate having the catalyst layer, and the unnecessary part is blown away with a blower, and the material is applied to a portion corresponding to 70% of the total length of the partition wall. It is heated and dried in a 120°C dryer for 2 hours, and after removing the moisture, it is fired in an electric furnace at 500°C for 2 hours to form an entry side lower layer from the upstream side along the cylinder axis direction X.
[0125] Next, Rh nitrate solution (0.2 g / L-cat in terms of Rh), non-OSC material (Db=7 μm, 40 g / L-cat), OSC material (Da=3 μm, 40 g / L-cat) and Al2O3-based binder are dispersed in an aqueous solvent and stirred to prepare slurry 7. Next, slurry 7 is flowed into the upstream end of the substrate, and the unnecessary part is blown away with a blower, and the material is applied to a portion equivalent to 80% of the total length of the partition wall. It is heated and dried in a dryer at 120°C for 2 hours, and after removing the moisture, it is fired in an electric furnace at 500°C for 2 hours to form an upper layer from the upstream side along the cylinder axis direction X. In this way, a catalyst for exhaust gas purification of Example 3 is obtained, which has three catalyst layers: an inlet side lower layer formed on the upstream side of the substrate surface, an outlet side lower layer formed on the downstream side of the substrate surface, and an upper layer formed on the surface of the inlet side lower layer and the outlet side lower layer. Furthermore, with respect to the lower layer of Example 3, when the OSC material is set to 100 parts by mass, the content ratio of the non-OSC material is 130 parts by mass (non-OSC material: OSC material = 13:10), and with respect to the upper layer, when the OSC material is set to 100 parts by mass, the content ratio of the non-OSC material is 100 parts by mass (non-OSC material: OSC material = 1:1).
[0126] (Examples 4 to 9, Comparative Examples 3 to 7, 9)
[0127] Exhaust purification catalysts of Examples 4 to 9 and Comparative Examples 3 to 7 and 9 were obtained by the same operation as in Example 3 except that materials having average particle diameters Da and Db shown in Table 3 were used as non-OSC materials and OSC materials, respectively, when forming the inlet side lower layer and the outlet side lower layer.
[0128] (Comparative Example 8)
[0129] When forming the lower layer on the inlet side and the lower layer on the outlet side, two kinds of powders with different average particle sizes Db were used as non-OSC materials at a volume ratio of 1:1 (La2O3-Al2O3 composite oxides with average particle sizes Db = 0.5μm and 40μm), and two kinds of powders with different average particle sizes Da were used as OSC materials at a volume ratio of 1:1 (CeO2-ZrO2 composite oxides with average particle sizes Da = 0.5μm and 9μm), except that the same operation was performed as in Example 3 to obtain the exhaust gas purification catalyst of Comparative Example 8. In addition, the average particle sizes Da and Db are the arithmetic averages of the two kinds of powders. In addition, the same operation as in Test Example 1 was performed to measure the average particle sizes Dx and Dy of the supporting material and evaluate the NOx purification performance. The results are shown in Table 3.
[0130] [Table 3]
[0131] Table 3 Research on the lower class
[0132]
[0133] Figure 5 It is a graph showing the relationship between the ratio of the average particle size of the supporting material (Dx / Dy) and NOx-T50. In the exhaust purification catalysts of Examples 3 to 9, the lower layer satisfies 1.5μm≤Dx and Dy<Dx. In the exhaust purification catalysts of Comparative Examples 3 to 8, both the upper layer and the lower layer do not satisfy at least one of 1.5μm≤Dx and Dy<Dx. Figure 5 As shown in Table 3, the NOx-T50 of the exhaust gas purification catalysts of Examples 3 to 9 is relatively low compared to the exhaust gas purification catalysts of Comparative Examples 3 to 8. That is, the NOx purification performance after durability is high. In addition, for Examples 3 to 9 and Comparative Examples 3 to 8, the same trend was also confirmed when the ratio of the OSC material to the non-OSC material in the lower layer was made non-OSC material: OSC material = 1:4 (when the OSC material is set to 100 parts by mass, the content ratio of the non-OSC material is 25 parts by mass).
[0134] Figure 7 This is a graph showing the relationship between the average particle size Dx of the OSC material and NOx-T50. Figure 6 Graph showing the relationship between the average particle size Dy of non-OSC materials and NOx-T50. Figure 7 As shown, for example, when the average particle size Dy of the non-OSC material is about 1 μm (e.g., 1±0.5 μm), the average particle size Dx of the OSC material is preferably about 2 to 10 μm. Figure 6 As shown, for example, when the average particle size Dx of the OSC material is about 2 μm (for example, 2±0.5 μm), the average particle size Dy of the non-OSC material is preferably 3 μm or less, for example, about 0.3 to 2 μm.
[0135] [Test Example 4: Study on the Catalyst Supporting Position in the Lower Layer of the Upper and Lower Two-Layer Structure]
[0136] (Comparative Example 10)
[0137] The exhaust gas purification catalyst of Comparative Example 10 was obtained by the same operation as in Example 3 except that the catalyst metal was not supported in the non-OSC material when forming the inlet side lower layer and the outlet side lower layer. In addition, the average particle diameter Dx and Dy of the supported material and the evaluation of NOx purification performance were carried out in the same manner as in Test Example 1. The results are shown in Table 4.
[0138] [Table 4]
[0139] Table 4 Study on the catalyst support position in the lower layer
[0140]
[0141] As shown in Table 4, compared with the exhaust gas purification catalyst of Comparative Example 10 in which the catalyst metal is carried only on the OSC material, the NOx-T50 of the exhaust gas purification catalyst of Example 3 in which the catalyst metal is carried on the non-OSC material and the OSC material is significantly lower. That is, the NOx purification performance after durability is high. As a reason for this, it can be considered that when the catalyst metal is carried only on the OSC material, the catalyst metal becomes too dense on the OSC material because the existence position of the catalyst metal is limited, and the catalyst metal is easily degraded during durability (for example, sintering accompanied by grain growth).
[0142] [Test Example 5: Study on the Catalyst Supporting Position in the Lower Layer of the Upper and Lower Two-Layer Structure]
[0143] (Example 10)
[0144] The exhaust gas purification catalyst of Example 10 was obtained in the same manner as in Example 3 except that a material having an average particle diameter Db of 0.5 μm was used as the non-OSC material and a material having an average particle diameter Da of 12 μm was used as the OSC material when forming the upper layer. In addition, the average particle diameters Dx and Dy of the supported material were measured and the NOx purification performance was evaluated in the same manner as in Test Example 1. The results are shown in Table 5.
[0145] [Table 5]
[0146] Table 5 Research on the upper layer
[0147]
[0148] In the exhaust purification catalyst of Example 10, both the upper layer and the lower layer satisfy 1.5μm≤Dx and Dy<Dx. In the exhaust purification catalyst of Example 3, only the lower layer satisfies 1.5μm≤Dx and Dy<Dx. As shown in Table 5, compared with the exhaust purification catalyst of Example 3, the exhaust purification catalyst of Example 10 has a lower NOx-T50. That is, the NOx purification performance after durability is high. However, the performance difference between the two is limited (small) compared with the difference between Examples 3 to 9 and Comparative Examples 3 to 9, for example. It can be inferred that in the case where the exhaust purification catalyst has a catalyst layer with a stacked structure of more than two layers, by making the lower layer satisfy Dy<Dx, the effect of the technology disclosed here can be better exerted.
[0149] Some embodiments of the present invention have been described above, but the above embodiments are merely examples. The present invention can be implemented in various other ways. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in the field. The technology described in the scope of the claim also includes various deformation and modification methods of the above-mentioned exemplified embodiments. For example, a part of the above-mentioned embodiment can be replaced by other deformation methods, and other deformation methods can be added to the above-mentioned embodiment. In addition, parts that are not described as necessary technical features can also be appropriately deleted.
[0150] Explanation of symbols
[0151] 1: exhaust purification system; 10, 30: catalyst for exhaust purification; 11, 31: substrate; 20, 40: catalyst layer; 21: supporting material; 22: OSC material; 23: non-OSC material (carrier other than OSC material); 41: lower layer; 41a: inlet side lower layer; 41b: outlet side lower layer; 42: upper layer.
Claims
1. A catalyst for exhaust gas purification, characterized in that: A substrate and a catalyst layer disposed on the substrate, The catalyst layer comprises a catalyst metal and a supporting material for supporting the catalyst metal. The supporting material comprises an OSC material having oxygen storage capacity and a carrier other than the OSC material, The volume-based average particle size Dx of the OSC material obtained by electron microscope observation is 1.5 μm or more, and is larger than the volume-based average particle size Dy of the carrier other than the OSC material obtained by electron microscope observation, and the average particle size Dy is 0.7 μm or more and 2 μm or less, The average particle size Dx and the average particle size Dy refer to the particle size corresponding to 50% accumulation from the smaller particle size side in the volume frequency distribution based on volume obtained by analyzing the observed image obtained by electron microscope observation of the cross section of the catalyst layer using image processing software Image J.
2. The exhaust gas purification catalyst according to claim 1, characterized in that: A ratio Dx / Dy of the average particle size Dx of the OSC material to the average particle size Dy of a carrier other than the OSC material is 1.3 or more and 20 or less.
3. The exhaust gas purification catalyst according to claim 1 or 2, characterized in that: When the OSC material is 100 parts by mass, the content ratio of the carrier other than the OSC material is 25 to 200 parts by mass.
4. The exhaust gas purification catalyst according to claim 1 or 2, characterized in that: The average particle size Dx of the OSC material is 15 μm or less.
5. The exhaust gas purification catalyst according to claim 1 or 2, characterized in that: The OSC material is a Ce-containing oxide including cerium oxide.
6. The exhaust gas purification catalyst according to claim 1 or 2, characterized in that: The support other than the OSC material is an Al-containing oxide including alumina.
7. The exhaust gas purification catalyst according to claim 1 or 2, characterized in that: The catalyst layer is formed on the surface of the substrate, A second catalyst layer containing the catalyst metal of a different type from that of the first catalyst layer is formed on the catalyst layer.
8. The exhaust gas purification catalyst according to claim 7, characterized in that: The catalyst layer contains Pd as the catalyst metal, The second catalyst layer contains Rh as the catalyst metal.
9. The exhaust gas purification catalyst according to claim 1 or 2, characterized in that: The catalyst layer has the catalyst layers having different compositions on the upstream side and the downstream side, respectively, in the flow direction of the exhaust gas from the inlet into which the exhaust gas flows toward the outlet out of the exhaust gas.
10. The exhaust gas purification catalyst according to claim 9, characterized in that: When the catalyst layer is divided into two parts in the flow direction of the exhaust gas, the side close to the inlet is the front section and the side close to the outlet is the rear section, The front section includes more carriers other than the OSC material than the back section.
Citation Information
Patent Citations
Catalyst for purifying exhaust gas
JP1997253454A
Catalyst for exhaust gas purification
JP2017189735A
Determination program, determination device, and determination method
JP2019159780A
Exhaust gas purification catalyst
WO2015037613A1
Exhaust gas purifying catalyst and method for producing same
CN102395428A